Intercropping with Pigeonpea (Cajanus cajan L. Millsp.): An Assessment of Its Influence on the Assemblage of Pollinators and Yield of Neighbouring Non-Leguminous Crops - Ujjwal Layek; Arijit Kundu; Nandita Das; Rajib Mondal; Prakash Karmakar (Life, 2023)
Intercropping is practiced in modern intensive agriculture considering many benefits, including additive crop yield. However, it may have competitive or facilitative interactions between pollinator-dependant crops. Here, we investigated the reproductive aspects of pigeonpea (Cajanus cajan). We assessed the influence of blooming pigeonpea on pollinator’s assemblage and the yield of neighbouring non-leguminous crops (e.g., coriander, mustard). For these, we recorded floral visitors and the yield of the targeted crops from two types of fields―closely situated and distantly situated concerning pigeonpea plantation. Pigeonpea is autogamous, but pollinator’s visits enhance fruit and seed sets. Bright, nectariferous flowers emitted several volatile organic compounds and were visited by numerous insect species. The prime pollinators of pigeonpea are carpenter bees and leafcutter bees. In contrast, halictidae, honeybees and stingless bees mainly pollinate the co-blooming non-leguminous crops (coriander and mustard). The richness and abundance of pollinators on these co-blooming crops remain similar in closely situated and distantly situated fields. As a result, the yield of the neighbouring crops is not significantly influenced by the blooming pigeonpea. Therefore, it can be concluded that planting pigeonpea in ridges of agricultural fields will be an additional agricultural output without affecting the assemblage of pollinators and yields of neighbouring co-blooming crops.